Pharmacotherapeutic options for pancreatic ductal adenocarcinoma. (12th December 2022) - Sardar, Muhammad; Recio-Boiles, Alejandro; Mody, Kabir; Karime, Christian; Chandana, Sreenivasa R; Mahadevan, Daruka; Starr, Jason; Jones, Jeremy; Borad, Mitesh; Babiker, Hani
ABSTRACT: Introduction: Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy projected to be the 2 nd leading cause of cancer related death in the USA by 2030. This manuscript discusses current and evolving treatment approaches in patients with pancreatic cancer. Areas covered: PDAC is classified as: a) resectable, b) borderline resectable, c) unresectable (locally advanced and metastatic). The standard of care for patients who present with resectable pancreatic adenocarcinoma is six months of adjuvant modified (m) FOLFIRINOX, gemcitabine plus capecitabine, or single agent gemcitabine. For many reasons, there has been a paradigm shift to employing neoadjuvant chemotherapy. For resectable and borderline resectable patients, we generally start with systemic therapy and reevaluate resectability with subsequent scans specifically when the tumor is located in the head or body of the pancreas. Combined chemoradiation therapy can be employed in select patients. The standard of care for metastatic PDAC is FOLFIRINOX or gemcitabine and nab-paclitaxel. Germline and somatic genomic profiling should be obtained in all patients. Patients with a germline BRCA mutation can receive upfront gemcitabine and cisplatin. Expert opinion: Thorough understanding of molecular pathogenesis in PDAC has opened various therapeutic avenues. We remain optimistic that future treatment modalities such as targeted therapies, cellular therapies and immunotherapy will further improve survival in PDAC.